Chlorpromazine Hydrochloride Determinations by Spectrophotometric Method via Oxidation with Sodium Periodate. (Journal of the College of Basic Education, 2019)
Phenothiazine rings are regarded a nucleus or basic compounds for its derivatives, such as chlorpromazine that are used as best drugs in antiemetic and antipsychotic. Chlorpromazine hydrochloride could be determined by many analytical techniques published. But in the present study it can be determined in raw material powder, depending on oxidation via NaIO4 by a simple, sensitive and rapid spectrophotometric method, for determination small amount of chlorpromazine hydrochloride in acidic aqueous solution. The results of this work demonstrated a formation new peak at scanning (1100-200) nm that appears in visible region (526) nm, with intensive rose color through oxidation of chlorpromazine with oxidative agent (NaIO4), and is stable for 2hours. And calibration curve for this reaction which was found obeyed Lamberts Beer law in concentration range (5-60) µg/ml of drug at optimum pH (1.5) and preferable concentration (10 µg/ml) of NaIO4; to give desirable analytical statistical value that equal to (DL=7 µg/ml, sensitivity=0.3 µg/ml).